2019
DOI: 10.48550/arxiv.1909.09434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of the Dark LMA solution and Fourth Sterile Neutrino for Neutrino-less Double Beta Decay

K. N. Deepthi,
Srubabati Goswami,
Vishnudath K. N.
et al.

Abstract: We analyze the effect of the Dark-large mixing angle (DLMA) solution on the effective Majorana mass (m ββ ) governing neutrino-less double beta decay (0νββ) in the presence of a sterile neutrino. We consider the 3+1 picture, comprising of one additional sterile neutrino. We have checked that the MSW resonance in the sun can take place in the DLMA parameter space in this scenario. Next we investigate how the values of the solar mixing angle θ 12 corresponding to the DLMA region alter the predictions of m ββ inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This degenerate solution to the solar mixing problem is often referred to as dark LMA (DLMA) solution in the literature [9][10][11]. Several studies have been done in the context of this DLMA solution, for example, the impact of DLMA in determining neutrino mass hierarchy at neutrino oscillation experiments [11][12][13][14][15], the impact of DLMA on 0νββ lifetime with three neutrinos [16], 3 + 1 neutrinos [17]. Further studies related to resolving the degeneracy were done by the authors of [10,18] while the constraints from COHERENT experiment (coherent neutrino nucleus scattering data) on DLMA solution were studied in [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This degenerate solution to the solar mixing problem is often referred to as dark LMA (DLMA) solution in the literature [9][10][11]. Several studies have been done in the context of this DLMA solution, for example, the impact of DLMA in determining neutrino mass hierarchy at neutrino oscillation experiments [11][12][13][14][15], the impact of DLMA on 0νββ lifetime with three neutrinos [16], 3 + 1 neutrinos [17]. Further studies related to resolving the degeneracy were done by the authors of [10,18] while the constraints from COHERENT experiment (coherent neutrino nucleus scattering data) on DLMA solution were studied in [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out above, the combined JUNO [60] measurement and Daya Bay [62,63] can significantly reduce the uncertainties from the oscillation parameters to make them negligibly small compared with the uncertainties from the decay measurement itself. So, we fix the oscillation parameters ( , , , and ) to their current best-fit values [10,11] in the following discussions.…”
Section: The Solar Octantmentioning
confidence: 99%
“…The two Majorana CP phases are then determined/constrained within some contour. Again, the JUNO [60] and Daya Bay [63] experiments can play an important role by significantly reducing the experimental uncertainties from the oscillation parameters.…”
Section: The Two Majorana Cp Phasesmentioning
confidence: 99%
“…It is shown that this DLMA solution is the manifestation of a generalized hierarchy degeneracy [5,[8][9][10]. In the study of neutrino less double beta decay, impact of the DLMA solution on the effective neutrino mass has been highlighted in [11][12][13].…”
Section: Introductionmentioning
confidence: 99%